Management Options for Patients with Chronic Back Pain without an Etiology - Lenny D. Salzberg; Eron G. Manusov (SAGE Publishing, 2013)
The treatment and management of low back pain is complex when there is no specific etiology such as cancer, fracture, or herniated disc. An organized approach to management that follows evidence based guidelines will facilitate care in a problem that reflects a lifetime prevalence of over 70 percent. The purpose of this review is to present a guideline to care for a common disabling process with a very heterogeneous etiology.